Maculopathy in patients with diabetes mellitus type 1 and type 2: associations with risk factors. Issue 8 (1st August 2000) - Zander, Eckhard; Herfurth, Sabine; Bohl, Beate; Heinke, Peter; Herrmann, Uwe; Kohnert, Klaus-Dieter; Kerner, Wolfgang
Abstract : AIM: To examine possible relation between diabetic maculopathy and various risk factors for diabetic complications in patients with diabetes mellitus type 1 and type 2. METHODS: Cross sectional study of two cohorts of diabetic patients, comprising 1796 patients with type 1 diabetes (mean age 47 years, mean duration of diabetes 24 years) and 1563 patients with type 2 diabetes (mean age 62 years, mean duration of diabetes 16 years). Retinopathy levels (R0–RV) and maculopathy were assessed by fluorescence angiography and fundus photography and binocular biomicroscopy. Diabetic neuropathy was assessed by means of computer assisted electrocardiography and by thermal and vibratory sensory examination. Patients were classified as normoalbuminuric (<20 μg/min) or microalbuminuric (20–200 μg/min) according to their albumin excretion rates measured in urine collected overnight. Using univariate analyses, the effects of selected patient characteristics on the presence of maculopathy were evaluated. Multiple logistic regression analyses were performed to determine independent effects of risk variables on diabetic maculopathy. RESULTS: Background retinopathy (RII) was found to be present in 28% of type 1 diabetic patients and in 38% of type 2 diabetic patients. The prevalence of maculopathy in these patients was remarkably high (42% in type 1 and 53% in type 2 diabetic patients). Patients with maculopathy had significantly impaired visual acuity. Multiple logistic correlation analysis revealed that in both types of diabetes maculopathy exhibited independent associations with duration of diabetes and with neuropathy (p <0.01); in type 1 diabetic patients there were significant associations with age at diabetes onset, serum triglyceride and total cholesterol levels (p <0.05); in type 2 diabetes with serum creatinine levels and with hypertension (p <0.05). CONCLUSIONS: Irrespective of the type of diabetes, diabetic patients with long standing diabetes have a high risk for the development of diabetic maculopathy. Diabetic maculopathy is closely associated with diabetic nephropathy and neuropathy and with several atherosclerotic risk factors which suggests that these factors might have an important role in the pathogenesis of maculopathy. However, prospective trials are necessary to evaluate the predictive value of such factors. The findings of the present cross sectional study reinforce the arguments of previous studies by others for tight control of hypertension and hyperglycaemia.